Secondary Histiocytic Sarcoma in a Pre-B-Acute Lymphoblastic Leukemia - Sharanya Ramakrishnan; Vivek Radhakrishnan; Aaishwarya Dhabe; Mayur Parihar; Lateef Zameer; Neeraj Arora; Reena Nair (Indian Journal of Medical and Paediatric Oncology)
Histiocytic sarcoma (HS) is a rare malignancy with grave prognosis. Adult acute lymphoblastic leukemia (ALL) patients developing HS as a secondary malignancy reported in the literature is even rarer. Through our case report, we aim to describe an adult pre-B-ALL patient who subsequently developed extensive HS while on maintenance therapy. We present the course of the disease, the management, and the resultant outcome. Active reporting of the course and management of secondary HS in adult ALL patients need to be emphasized to gain better insight into the presentation and the course of the disease, incidence as well as molecular pathology, especially given the relative silence of the literature in this regard.